Admission to long-stay residential care and mortality among people with and without dementia living at home but on the boundary of residential care: a competing risks survival analysis. (3rd October 2021) - Carter, L.; O'Neill, S.; Austin, Peter C.; Keogh, F.; Pierce, M.; O'Shea, E.
Abstract: Background: Health policy in many countries is underpinned by a commitment to support dependent older people to remain in their own home for as long as possible and practicable. This study explores factors affecting both admission to long-stay residential care (LSRC) and mortality among people with and without dementia who are currently living at home with intensive formal care support. Methods: This is a cross-sectional study based on administrative data collected on 429 dependent older people in Ireland, 269 of whom were people with dementia. A cause-specific hazard model was used to investigate the hazard of admission to LSRC, while accounting for mortality as a competing risk and vice versa. Results: Admission to LSRC was higher for people with dementia relative to people without and for those receiving lower amounts of informal care. The hazard of mortality was significantly higher for older people aged 85+, whereas it was lower for individuals with a medium level of dependency relative to those with high levels of dependency. The hazard of mortality was also influenced by the amount of informal care provision. Conclusion: People with dementia are more likely to be admitted to LSRC than people without. Care for people with dementia needs to be more specialised and personal, and intensity of provision should not be equated to the number of care hours on offer. Informal care provision may help to prevent admission to LSRC. Advanced age, physical dependency and informal care provision affect mortality, raising interesting issues in relation to resource allocation.